Birth of a healthy child fathered by a man with Klinefelter's syndrome after preimplantation genetic testing - Trninić-Pjević, Aleksandra; Milatović, Stevan; Havrljenko, Jelena; Kavecan, Ivana; Kopitović, Aleksandar (Vojnosanitetski pregled, 2021)
Introduction. Most men with non-mosaic Klinefelterʼs syndrome (KS; 47, XXY) have azoospermia, and were until recently considered completely infertile. However, it has been confirmed that some non-mosaic patients had spermatozoa in the ejaculate, although severe oliogasthenoteratosoospermia was present in all of them. Although a high fertilization rate with an intracytoplasmic sperm injection (ICSI) procedure using sperm from a non-mosaic patient and the cumulative pregnancy rate following in vitro fertilization constitute 53%, the incidence of live births after ICSI using sperm of men with non-mosaic KS is very low: 1 in 8 cases. Case report. At the Clinical Centre of Vojvodina’s Department of Gynecology and Obstetrics, a successful in vitro fertilization treatment was conducted using the sperm of a man with KS non-mosaic syndrome. Preimplantation genetic testing was performed for the embryo selection, and an euploid embryo was transferred in the subsequent natural cycle. Delivery of male newborn was spontaneous, vaginal, with head presentation, after 40 weeks and 3 days. The newborn’s Apgar score was 10/10. His birth weight was 3,950 g, and his length was 55 cm. At 12 months of age, his psychomotor development was assessed as normal on the Brunet-Lézine psychomotor development scale. Conclusion. Due to an increased risk of chromosomal abnormalities (abnormalities of sex or autosomal chromosomes) in embryos from couples with KS males, preimplantation genetic testing is conducted to select a chromosomally normal embryo. This may help achieve pregnancy sooner, decrease the chance of multiple pregnancy and its potential complications, decrease the risk of miscarriage, and reduce the need for invasive prenatal diagnostic procedures and the risks of other complications, as well as the risk of late termination of pregnancy in case of pathological findings of the fetal karyotype using conventional diagnostic procedures.
Keywords: klinefelter syndrome; reproductive techniques, assisted; fertility; sperm injections, intracytoplasmatic; azoospermia, non-obstructive; preimplantation diagnosis